Effects of Milk Storage Temperature at the Farm on the Characteristics of Parmigiano Reggiano Cheese: Chemical Composition and Proteolysis - Franceschi, Piero (Animals (Basel), 2021)
SIMPLE SUMMARY: Parmigiano Reggiano is a Protected Designation of Origin (PDO) hard-cooked cheese made from raw milk that is ripened from 18 to over 24 months. Since the EU official protocol does not allow farmers to store the milk at the farm at a temperature lower than 18 °C, the conditions applied during storage strongly affect milk quality and suitability to cheese-making. At this temperature, the bacterial growth and the activity of proteolytic enzymes, responsible for milk alteration, cannot be inhibited. The aim of this research was to study the effect of storing milk at 9 °C, at the farm, on the chemical characteristics, proteolysis and organic acid profile of Parmigiano Reggiano cheese during ripening. The obtained results revealed lower fat and higher protein contents with respect to the cheese produced with milk stored at 20 °C. Regarding proteolysis, peptone nitrogen was the only parameter that significantly increased in the cheese produced with the milk stored at 9 °C. Despite of the statistical significance of the differences observed, they appeared as too small for changing the overall “typicality” of the cheese, and should be included within the ordinary range of variability of Parmigiano Reggiano. ABSTRACT: Parmigiano Reggiano is a Protected Designation of Origin (PDO) cheese whose official production protocol provides that milk cannot be stored at less than 18 °C at the farm. The possibility of refrigerating milk at the farm is highly debated, since it should allow for the limiting of bacterial growth, thus improving the quality of the cheese. The present research aimed to study the influence of storing the milk at 9 °C on the chemical composition and proteolysis during the ripening of Parmigiano Reggiano cheese. The experimentation considered six cheese-making trials, in which both evening and morning milks were subdivided into two parts that were maintained at 9 and 20 °C. After Parmigiano Reggiano cheese-making, one of the twin wheels obtained was analyzed after 21 months of ripening. From each cheese, two different samples were taken, one from the inner zone, and the other from the outer zone. The results of the chemical analyses evidenced that milk storage at 9 °C significantly (p ≤ 0.05) influenced fat, crude protein, soluble nitrogen and peptone nitrogen contents. Nevertheless, the differences observed with respect to the cheese obtained with milk stored under standard condition were very small and should be considered within the “normal variations” of Parmigiano Reggiano chemical characteristics.